2001
DOI: 10.1038/sj.bjp.0703929
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanisms that mediate reactive hyperaemia in guinea‐pig hearts: role of KATP channels, adenosine, nitric oxide and prostaglandins

Abstract: 1 Reactive hyperaemia is a transient vasodilatation following a brief ischaemic period. ATPdependent K + (K ATP ) channels may be important in mediating this response, however it is unclear whether mitochondrial K ATP channels contribute to this in the heart. 2 We examined the involvement of K ATP channels and the relative role of mitochondrial channels as mediators of coronary reactive hyperaemia and compared them to mechanisms involving NO, prostaglandins and adenosine in the guinea-pig isolated heart. 3 Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…1-3 the use of a traditional cardioplegic solution, Bretschneider HTK, also did not offer good endothelial preservation in the whole heart as indicated by three independent indices of coronary regulatory functions (vasodilations toward bradykinin and ATP, reactive hyperaemic response). Reactive hyperaemia is largely mediated by activation of K + ATP channels, most likely present on vascular smooth muscle cells, and involvement of the myocardial metabolite adenosine [15]. Bradykinin has been shown to act via stimulation of endothelial NO release [16].…”
Section: Discussionmentioning
confidence: 99%
“…1-3 the use of a traditional cardioplegic solution, Bretschneider HTK, also did not offer good endothelial preservation in the whole heart as indicated by three independent indices of coronary regulatory functions (vasodilations toward bradykinin and ATP, reactive hyperaemic response). Reactive hyperaemia is largely mediated by activation of K + ATP channels, most likely present on vascular smooth muscle cells, and involvement of the myocardial metabolite adenosine [15]. Bradykinin has been shown to act via stimulation of endothelial NO release [16].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular K ATP channels have also been implicated in the coronary vasodilatory response to exercise 15 and hypoxia. 16 K ATP channels may also play a role in endotoxic vasodilation. 17 Independent gene targeting studies in mice of either the gene encoding SUR2 (ABCC9) or Kir6.1 (KCNJ8) produced an identical phenotype of coronary artery spasm seen as transient ST segment elevation accompanied by atrioventricular heart block, bradycardia, and sudden death.…”
mentioning
confidence: 99%
“…The K ATP channel has been reported to be involved in coronary ischemic vasodilation (24,41,42,57), although its role in metabolic vasodilation remains controversial (13,15,23,35,47,55). In isolated mouse hearts, the present study showed that glibenclamide (5 M) significantly reduced CF (by ϳ45%; Fig.…”
Section: Discussionmentioning
confidence: 56%